2008
DOI: 10.1002/adsc.200700550
|View full text |Cite
|
Sign up to set email alerts
|

α,β‐Unsaturated Aldehydes as Substrates for Asymmetric CC Bond Forming Reactions with Thiamin Diphosphate (ThDP)‐Dependent Enzymes

Abstract: The enzymes benzaldehyde lyase (BAL) from Pseudomonas fluorescens, benzoylformate decarboxylase (BFD) from Pseudomonas putida and pyruvate decarboxylase (PDC) from Saccharomyces cerevisiae provide different C À C bond forming possibilities of a,b-unsaturated aldehydes with aliphatic and aromatic aldehydes. Structure elucidation and determination of the absolute configuration of the products, which were obtained with high regio-and stereoselectivity were carried out. Selective 1,2-reactivity with yields of 75% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 56 publications
1
39
0
2
Order By: Relevance
“…For example, in previous studies we have noted that 2,3-alkanediones are frequently present in aeration samples that contain 3-hydroxyalkan-2-ones ). Although both (E)-2-hydroxy-4-octen-3-one and (E)-3-hydroxy-4-octen-2-one have been reported as synthetic products from enzyme-catalyzed reactions of α,β-unsaturated aldehydes with aldehydes (Cosp et al 2008), to our knowledge, neither has been identified from natural sources before.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, in previous studies we have noted that 2,3-alkanediones are frequently present in aeration samples that contain 3-hydroxyalkan-2-ones ). Although both (E)-2-hydroxy-4-octen-3-one and (E)-3-hydroxy-4-octen-2-one have been reported as synthetic products from enzyme-catalyzed reactions of α,β-unsaturated aldehydes with aldehydes (Cosp et al 2008), to our knowledge, neither has been identified from natural sources before.…”
Section: Discussionmentioning
confidence: 97%
“…1 H NMR δ 7.02 (dt, J=15.6, 7.0 Hz, 1H), 6.20 (dt, J=16.0, 1.6 Hz, 1H), 4.42 (dq, J=7.0, 5.6 Hz, 1H), 3.63 (d, J=5.2 Hz, 1H), m (2.25-2.19, 2H), m (1.55-1.46, 2H), 1.35 (d, J=6.8 Hz, 3H), 0.93 (t, J=7.2 Hz, 3H). The 1 H NMR spectrum was in agreement with that previously reported (Cosp et al 2008). The enantiomers were separated by 0.8 min on the Cyclodex B GC column.…”
Section: Sources Of Chemicalsmentioning
confidence: 96%
See 1 more Smart Citation
“…Beispielhaft sollen hier drei Enzyme ausführlicher besprochen werden: die Pyruvatdecarboxylase (PDC) aus Zymomonas mobilis [6,7], die Benzaldehydlyase (BAL) aus P. fluorescens [8][9][10][11][12][13][14] und die verzweigtkettige Ketosäuredecarboxylase (KdcA) aus Lactococcus lactis [15,16].…”
Section: Ergebnisseunclassified
“…Es wurde wegen seiner leichten Zugänglichkeit, der höheren Stabilität und insbesondere aufgrund der Möglichkeit, die Synthese von (R)-Phenylacetylcarbinol (PAC) ausgehend von den Aldehyden Acetaldehyd und Benzaldehyd zu katalysieren, ausgewählt. Letzteres steht im Gegensatz zur PDC aus Hefe, die Ketosäuren wie Pyruvat als Ausgangsverbindung für die intrinsische Herstellung des Acetaldehyds benötigt [14]. Allerdings ist das bakterielle Enzym hinsichtlich seiner C-C-Verknüpfungs-aktivität weniger aktiv als das Enzym der Hefe.…”
Section: R-selektive Enzymeunclassified